Blending face-to-face communication and video blogging in acquiring public speaking skills / Vimala Devi Balakrishnan and Fatimah Puteh - Balakrishnan, Vimala Devi; Puteh, Fatimah (Universiti Teknologi MARA, Kedah, 2014)
Blended learning is a unique approach that ‘blends’ face-to-face classroom teaching with suitable use of technology or online resources. The online materials are part of the input or supplements for a language classroom. This paper aims to report on a study conducted on a group of 12 Diploma students, who studied public speaking as a component of their English language course. The purposes of the study are to identify the effectiveness of using technology, namely, video blog, in developing public speaking skills among the participants and to determine their perception on ‘blending’ face-to-face communication and video blog for learning public speaking skills. Data for the study were collected using questionnaire, blog entries, online reflection and semi structured interviews. Results of the study revealed that the participants have positive perception towards blending face-to-face communication and video blogging in acquiring public speaking skills. The findings also indicated that the incorporation of video blog is effective in developing their public speaking skills. Therefore, it can be concluded that blended learning method incorporating video blog and face-to-face instruction can be efficiently adapted in acquiring public speaking skills among students.